Membangun Karakter Guru Madrasah Tsanawiyah Salafiyah Syafi’iyah Sukorejo Situbondo - Rif‘ah , Rif‘ah (Jurnal Pendidikan Islam Indonesia, 2016)
The study conclude that. Firstly : the teacher character of madrasah is formed by three aspect, those are: vision, mission of pesantren/madrasah, inspiring figure (leader of pondok pesantren , chief of sector / chief of education religious, chief master of madrasah) and the culture of madrasah. The teacher profile of which the intuctional task is to hold about the establishment of madrasah teacher character, because vision and mission Pondok Pesantren and Madrasah, awakened from inspiration (leader of pondok pesantren, chief of sector / chief of education religious,chief master of madrasah) and grow because madrasah’s culture. Secondly : The teacher profile of wich the intractional task is to hold principle, by ikhlas and barokah, intent for practicing their knowledge and worship and not to gain salary. From the all of, is advisable by oll of teacher to perform their duties as teacher to apply their knowledge roby the full intention is not to gotten production. Don’t just be mu'allim, but should be murabby for the student. If it is done by oll of teacher, Insayaallah our students will be good character persion, finally purpse of education will be achieved by good education.